2017
DOI: 10.1002/hed.24714
|View full text |Cite
|
Sign up to set email alerts
|

Tumor volume as an independent predictive factor of worse survival in patients with oral cavity squamous cell carcinoma

Abstract: Among patients who already have advanced cancers, tumor volume can significantly impact their prognoses. © 2017 Wiley Periodicals, Inc. Head Neck 39: 960-964, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 65 publications
(129 reference statements)
0
13
0
1
Order By: Relevance
“…Tumour volume significantly predicted the disease-free and overall survival of patients with already advanced (T4a) OSCC. 38 A study by Mücke et al, including 437 OSCC patients, showed similar results, that is, tumour volume was significantly associated with the overall survival of the patients. 39…”
Section: Histopathological Factorsmentioning
confidence: 69%
“…Tumour volume significantly predicted the disease-free and overall survival of patients with already advanced (T4a) OSCC. 38 A study by Mücke et al, including 437 OSCC patients, showed similar results, that is, tumour volume was significantly associated with the overall survival of the patients. 39…”
Section: Histopathological Factorsmentioning
confidence: 69%
“…Although there are various advanced treatment options, recurrence rates are high. Local or regional relapse and cervical lymph node metastasis are threats to patients ( 12 ). Therefore, studies have been performed to elucidate the molecular mechanism of TSCC pathogenesis and explore potential biological markers of TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has demonstrated that many radiomic signatures show strong dependence on tumour volume 28,29 , which is a simple image-derived feature and a known prognostic factor in HNC 35 . We evaluated the correlation of all binary predictions with volume using Spearman rank correlation (fig.…”
Section: Impact Of Volume Dependence On Model Performancementioning
confidence: 99%